Comparison of the smiley face rod method versus intervertebral fusion for the treatment of L5 spondylolysis in adults - Dong, Qi-Yuan; Yang, Xue-Fei; Wu, Hai-Long; Shi, Yan; Yu, Li-Min; Huang, Yong-Can; Yu, Bin-Sheng (Frontiers in Medicine, 2024)
For patients who suffered from L5 spondylolysis and fail to improve using conservative treatment, the best surgical strategy remains controversial. This study compares the efficacy of the treatment of L5 spondylolysis using the smiley face rod (SFR) method versus intervertebral fusion (IF).We analysed 32 patients with L5 spondylolysis who underwent surgery in our department between January 2017 and June 2019, 14 patients in the SFR group and 18 patients in the IF group. The operation time, intraoperative blood loss, postoperative drainage time, length of stay and postoperative complications were compared. The pain VAS and ODI were evaluated before operation and at three months, six months and one year postoperatively. The changes in ROM in L4/5 and L5/S1 in these two groups before and after surgery were measured through imaging examinations and the bone graft fusion rate was assessed according to the Brown standard.The operation time of the SFR group was much shorter than that of the IF group , and the blood loss of the SFR group was significantly lower than that of the IF group. Length of stay in the SFR group was less than that of the IF group . No difference was found in the VAS and ODI scores between the two groups at three months, six months and one year after surgery. In the IF group, the ROM in L4/5 showed an obvious increase after surgery compared to that before surgery, and it was much bigger than that of the SFR group (P < .05). A notable reduction of ROM was seen in L5/S1 in the IF group compared to the SFR group (P < .05). The fusion rate of the isthmus in the SFR group was 79% at three months and 86% at six months after surgery. The SFR and IF both improve the clinical symptoms and quality of life of patients with L5 spondylolysis. However, the SFR technique had the advantages of a shorter operation time and less blood loss than IF; it could also preserve the ROM of the surgical segment and had little influence on adjacent segments in short-term follow-ups.